2007
DOI: 10.2174/092986707782360097
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Unified Pharmacophore Model of the Benzodiazepine Binding Site on γ-Aminobutyric Acida Receptors: Correlation with Comparative Models

Abstract: A successful unified pharmacophore/receptor model which has guided the synthesis of subtype selective compounds is reviewed in light of recent developments both in ligand synthesis and structural studies of the binding site itself. The evaluation of experimental data in combination with a comparative model of the alpha1beta2gamma2 GABA(A) receptor leads to an orientation of the pharmacophore model within the Bz BS. Results not only are important for the rational design of selective ligands, but also for the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
82
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(99 citation statements)
references
References 103 publications
(119 reference statements)
11
82
0
4
Order By: Relevance
“…A novel approach to achieve this goal was developed by Cook and coworkers in the 1980s (1,25) that employed a pharmacophore/receptor model based on the binding affinity of rigid ligands to BDZ/GABA A receptor sites (8). From this series of receptor models for ␣ 1-6 ␤3␥2 subtypes a robust pharmacophore for ␣5-subtype selective ligands emerged resulting in the synthesis of a novel ␣5␤3␥2 partial agonist modulator: (R)-ethyl 8-ethynyl-6-(2-fluorophenyl)-4-methyl-4H-benzo[f]imidazo [1,5-a] [1,4]diazepine-3-carboxylate (or SH-053-2=-F-R-CH 3 ) (10).…”
mentioning
confidence: 99%
“…A novel approach to achieve this goal was developed by Cook and coworkers in the 1980s (1,25) that employed a pharmacophore/receptor model based on the binding affinity of rigid ligands to BDZ/GABA A receptor sites (8). From this series of receptor models for ␣ 1-6 ␤3␥2 subtypes a robust pharmacophore for ␣5-subtype selective ligands emerged resulting in the synthesis of a novel ␣5␤3␥2 partial agonist modulator: (R)-ethyl 8-ethynyl-6-(2-fluorophenyl)-4-methyl-4H-benzo[f]imidazo [1,5-a] [1,4]diazepine-3-carboxylate (or SH-053-2=-F-R-CH 3 ) (10).…”
mentioning
confidence: 99%
“…Previously, evidence from the ligand-based GABA A R pharmacophore/receptor model and SAR 23,35 have indicated that subtle changes in the IBZD substituents affect the BzR/GABA(A)R subtype selectivity dramatically. For instance, loss of the methyl group at the C(4) position decreases the α5-subtype efficacy while the efficacy at α2/α3-β3γ2 GABA(A)ergic subtypes increases dramatically.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the ligand-receptor reaction is the opening of chloride channels and hyperpolarisation of the nervous membrane, leading to the clinical effects of anaesthesia, amnesia and anxiolysis . Barbiturates prolong the time of ion channel opening (initiated earlier by benzodiazepines) via synergism [28].…”
Section: Mechanisms Of the Neurotoxicity Of Anaestheticsmentioning
confidence: 99%